Balancing selection at nonself recognition loci in the chestnut blight fungus, Cryphonectria parasitica, demonstrated by trans-species polymorphisms, positive selection, and even allele frequencies. (December 2018) - Milgroom, Michael; Smith, Myron; Drott, Milton; Nuss, Donald
Abstract Balancing selection has been inferred in diverse organisms for nonself recognition genes, including those involved in immunity, mating compatibility, and vegetative incompatibility. Although selective forces maintaining polymorphisms are known for genes involved in immunity and mating, mechanisms of balancing selection for vegetative incompatibility genes in fungi are being debated. We hypothesized that allorecognition and its consequent inhibition of virus transmission contribute to the maintenance of polymorphisms in vegetative incompatibility loci (vic ) in the chestnut blight fungus, Cryphonectria parasitica . Balancing selection was demonstrated at two loci, vic2 andvic6, by trans-species polymorphisms inC. parasitica, C. radicalis, andC. japonica and signatures of positive selection in gene sequences. In addition, more than half (31 of 54) of allele frequency estimates at sixvic loci in nine field populations ofC. parasitica from Asia and the eastern US were not significantly different from 0.5, as expected at equilibrium for two alleles per locus under balancing selection. At threevic loci, deviations from 0.5 were predicted based on the effects of heteroallelism on virus transmission. Twenty-five of 27 allele frequency estimates were greater than or equal to 0.5 for the allele that confers significantly stronger inhibition of virus transmission at three loci with asymmetric transmission. These results are consistent with the allorecognition hypothesis that vegetative incompatibility genes are under selection because of their role in reducing infection by viruses.